AN ANALYSIS OF ERORR IN WRITING NARRATIVE TEXT MADE BY STUDENTS OF NINTH GRADE OF SMP NEGERI 4 FANAYAMA - Gee, Welfin (Universitas Nias Raya, 2024)
Narrative text tells about sequence of events in the past. Narrative text hone students to have the ability to think, imagine what the essence of a story and then retell it such as poetry, prose, song, theater, or dance. This research aimed at analyzing the errors made by students in writing narrative text at the ninth grade of SMP Negeri 4 Fanayama. This research was designed by using descriptive qualitative method. In analyzing the data, the researcher used Corder’s (1981) theory, they were identification of error, description of error, explanation of error, and evaluation of error. In this research, the source of the data was taken from 24 students of ninth grade of SMP Negeri 4 Fanayama. Techniques of the data collection were documentation and interview. The result of the research was students made errors in writing narrative text. The errors were made by students they are ommision errors (148), misformation (387), misordering (43), and errors on addition (59). The causes of the errors were intralingual transfer and context of learning. The primary cause of error was context learning. It was concluded that students did errors because the students understanding of English, especially grammar is still lacking. so the students did not completely understand and the students try to make wrong concept and hypotheses from the target language with their limited experience about it. Therefore suggested to the English teacher more explain narrative text material especially in grammar.